(untitled) (Journal of Applied Learning and Teaching, 2023)
This paper presents an analysis of an authentic writing assessment to externalise the knowledge, skills, and attitudes necessary for developing such assessments. Specifically, the paper examines a technical proposal writing assignment developed and used as a continual assessment in an undergraduate engineering course by employing an authentic assessment framework as the analytical lens. The findings showed that the framework can serve as a valuable guide in developing authentic writing assessments. Further, it became evident that achieving functional authenticity in all dimensions may not always be viable. Developing fully functionally authentic writing assessments/assignments for beginners is not always advisable, as completing such assignments may lead to cognitive overload. Therefore, it is recommended that both the dimensions of authenticity and students’ ability levels be considered when analysing, developing, and using authentic writing assessments and assignments. Indeed, striking the right balance between authenticity and students’ cognitive capacity is crucial for creating optimal learning experiences.